The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11113-016-9417-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cash Transfers on Fertility: Evidence from Argentina

Abstract: In 2009 Argentina introduced a large poverty-alleviation program (AUH) that provides monthly cash transfers per child to households without workers in the formal sector. In this paper we study the potential unintended effect of this program on fertility. We apply a difference-indifference strategy comparing the probability of having a new child among eligible and ineligible mothers both before and after the program inception. The intention to treat estimations suggest a significant positive impact on fertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 45 publications
0
37
0
1
Order By: Relevance
“…These results confirm those found by Talnan and Vimard (2003). However, this conclusion should be nuanced (Garganta et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results confirm those found by Talnan and Vimard (2003). However, this conclusion should be nuanced (Garganta et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…However, it is important to note that some authors have found positive relationships between poverty and fertility, whereas according to others, there is no significant relationship between these variables (Ainsworth, 1989). Applying a difference-in-difference strategy comparing the probability of having a new child among eligible and ineligible mothers both before and after the program inception, Garganta and al. (2016) find a significant and positive impact of cash transfers per child to households without workers in the formal sector on fertility in those households with at least one child, but no significant effect on childless households.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, Edo and Marchionni (2018) describe positive effects of UCA in intra-year drop out rates and primary education completion rates, with an even greater impact on girls aged 12-17, while less encouraging results on the same subject can be found in D'Elía & Navarro (2013). Garganta et al (2016) found that UCA may be related to a 2% increase of fertility rates in potential beneficiaries, though the program has not demographic objectives-at least explicitly. All of these studies focus on efficacy of UCA as an instrument.…”
Section: Rights Constitutional Rightsmentioning
confidence: 99%
“…Concerning the potential impact of AUH on schooling, the economic incentives introduced by the program and its conditions may both reduce the likelihood of beneficiary children dropping out of school and encourage dropouts to get back to the education system. Since the program covers a large proportion of Argentinian children and the cash transfer represents a large increase of household income for beneficiary families (Garganta et al, 2016), the impact on school attendance could be potentially strong. Nevertheless, only the empirical evidence can determine the actual relevance of this effect.…”
Section: Introductionmentioning
confidence: 99%